2021
DOI: 10.1001/jamaophthalmol.2021.0651
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Antiretinal Antibody Testing

Abstract: The clinical utility of most antiretinal antibodies (retina antibodies) currently available for testing remains unclear and unproven. Despite this, the presence of retinal antibodies is included in current diagnostic autoimmune retinopathy criteria.OBJECTIVE To evaluate the clinical significance of comprehensive retinal antibody evaluations currently offered in North America. DESIGN, SETTING, AND PARTICIPANTSIn this cross-sectional study, 14 patients without autoimmune retinopathy were recruited into the Mayo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…This case suggests that linezolid could also potentially cause retinal dysfunction, but further study is warranted. The autoantibodies in this case, however, likely represent a false-positive result considering one recent study found that 93% of patients positive for antiretinal antibodies did not have autoimmune retinopathy [36 ▪ ].…”
Section: Potential Retinal Involvementmentioning
confidence: 68%
“…This case suggests that linezolid could also potentially cause retinal dysfunction, but further study is warranted. The autoantibodies in this case, however, likely represent a false-positive result considering one recent study found that 93% of patients positive for antiretinal antibodies did not have autoimmune retinopathy [36 ▪ ].…”
Section: Potential Retinal Involvementmentioning
confidence: 68%
“…Chen et al found the presence of anti-retinal antibodies against at least one retinal antigen in 13 out of 14 patients without AIR, although 10 of these patients had macular or optic nerve disease. 42 Interestingly, none of these patients tested positive for anti-recoverin antibodies, suggesting that anti-recoverin antibodies may be possibly more specific to AIR. Given the high rate of positivity for anti-retinal antibodies even in patients without AIR, the presence of anti-retinal antibodies would need to be interpreted in the appropriate clinical context.…”
Section: Discussionmentioning
confidence: 92%
“…2,11 ARAs can be found in other ocular diseases such as retinitis pigmentosa, Vogt-Koyanagi-Harada, sympathetic ophthalmia, toxoplasma retinochoroiditis, diabetic retinopathy, exudative age-related macular degeneration, and cystoid macular edema as well as in systemic diseases such as systemic lupus erythematous, multiple sclerosis, Behcet's disease, and inflammatory bowel disease. 12 ARAs may also be absent in diagnosed patients and present in healthy patients 2,13,14 or patients with AIR quiescence for years. 15 Three laboratory techniques have been described for serum ARA detection, including immunohistochemistry (IHC), WB, and enzyme-linked immunosorbent assay (ELIZA), among which IHC and WB are more commonly used.…”
Section: Discussionmentioning
confidence: 99%